2022
DOI: 10.3390/vaccines10050744
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events and Safety Profile of the COVID-19 Vaccines in Adolescents: Safety Monitoring for Adverse Events Using Real-World Data

Abstract: A COVID-19 vaccine BNT162b2 (Pfizer-BioNTech) has recently been authorized for adolescents in the US. However, the impact of adverse events on adolescents after vaccination has not been fully investigated. To assess the safety of the COVID-19 vaccine in adolescents, the incidence of adverse events (AEs) in adolescents and adults was compared after vaccination. We included 6304 adolescents (68.14 per 100,000 people) who reported adverse events using vaccine adverse event reporting system (VAERS) data from 10 Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…Fifth, people under the age of 20 were excluded from the study because they were not eligible for the booster dose at the time of the study. There are only a few studies on young people; further study is needed to provide more data [ 24 , 25 , 26 ]. Sixth, our result only included short-term AE in the whole population.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, people under the age of 20 were excluded from the study because they were not eligible for the booster dose at the time of the study. There are only a few studies on young people; further study is needed to provide more data [ 24 , 25 , 26 ]. Sixth, our result only included short-term AE in the whole population.…”
Section: Discussionmentioning
confidence: 99%
“…The literature search screened 1296 studies of which 102 were reviewed in full text (Figure 1). A total of 43 studies were included in the meta-analyses, of which reported 16,978 cases of myocarditis [7,8, , 28,451 cases of myocardial infarction [8,19,20,43,47,50,[52][53][54][55][56][57][58] and 96,269 cases of cardiac arrhythmia [8,19,21,22,24,43,44] (Table S1). Overall risk of bias in these studies were rated as moderate to high quality (Tables S2 and S3).…”
Section: Search Results and Characteristics Of Included Studiesmentioning
confidence: 99%
“…However, the AE patterns of adolescents differed from those of the adults. Lee et al 81 analyzed data from the Korean vaccine AE reporting system to compare the risk and types of AEs in adolescents (aged 12–15) with those in adults. Compared to adults, adolescents had a higher incidence of encephalitis/myelitis, convulsions, GBS, myocarditis/pericarditis, lymphadenopathy, lymphopenia, and multisystem inflammatory syndrome.…”
Section: Adverse Events Of Covid-19 Vaccines In Koreamentioning
confidence: 99%